The Relationship between the Audit Outputs and Managerial Entrenchment - Hamideh Nazaridavaji; Raha Rajaei Khoramabad (Iranian Journal of Accounting, Auditing & Finance)
The present study investigates the relationship between audit outputs (including audit quality, type of opinion, audit fee, and timeliness) and managerial entrenchment in firms listed on the Tehran Stock Exchange. The multivariate regression model is used for hypothesis testing, research hypotheses were tested using a sample of 678 listed observations on the Tehran Stock Exchange during 2012-2017, and the exploratory factor analysis of 12 variables (including CEO duality, financial expertise, and CEO industry, board compensation, managerial ownership, tenure, and CEO consistency, board independence, financial expertise, and board industry, correlation and board effort) is used for examining managerial entrenchment. As expected, the results show a significant relationship between audit outputs and managerial entrenchment, such that audit fee and audit quality are negatively associated with managerial entrenchment, and the relationship between report delay and type of opinion and managerial entrenchment is positive and significant. By adding new variables to measuring managerial entrenchment, the present study provides a better evaluation of this index. Moreover, it contributes to the field because the previous studies have benefited from limited proxies for this purpose.